Polymorphism of Carbamazepine Pharmaceutical Cocrystal: Structural Analysis and Solubility Performance - Artem O. Surov; Ksenia V. Drozd; Anna G. Ramazanova; Andrei V. Churakov; Anna V. Vologzhanina; Elizaveta S. Kulikova; German L. Perlovich (MDPI AG, 2023)
Polymorphism is a common phenomenon among single- and multicomponent molecular crystals that has a significant impact on the contemporary drug development process. A new polymorphic form of the drug carbamazepine (CBZ) cocrystal with methylparaben (MePRB) in a 1:1 molar ratio as well as the drug's channel-like cocrystal containing highly disordered coformer molecules have been obtained and characterized in this work using various analytical methods, including thermal analysis, Raman spectroscopy, and single-crystal and high-resolution synchrotron powder X-ray diffraction. Structural analysis of the solid forms revealed a close resemblance between novel form II and previously reported form I of the [CBZ + MePRB] (1:1) cocrystal in terms of hydrogen bond networks and overall packing arrangements. The channel-like cocrystal was found to belong to a distinct family of isostructural CBZ cocrystals with coformers of similar size and shape. Form I and form II of the 1:1 cocrystal appeared to be related by a monotropic relationship, with form II being proven to be the thermodynamically more stable phase. The dissolution performance of both polymorphs in aqueous media was significantly enhanced when compared with parent CBZ. However, considering the superior thermodynamic stability and consistent dissolution profile, the discovered form II of the [CBZ + MePRB] (1:1) cocrystal seems a more promising and reliable solid form for further pharmaceutical development.